Critical Review on Broad Spectrum Action of Vasti Karma - A Literary Study - Harshamali K.A.D.T,; Tharangani W.A.S, (AYUSHDHARA, 2023)
Ayurveda views a person's Tridosha balance as indicative of their overall health, and Pancakarma treatment aims to restore harmony and normality by purging the vitiated Dosha. One of the five Pancakarma procedures, Vasti karma is a unique and broad spectrum therapeutic and preventive strategy. The objective of this study was to determine why Vasti karma has emerged as a key Panchakarma therapeutic strategy. The study's data sources included primary Ayurvedic texts, secondary Ayurvedic medical literature, and scientific publications that were published online. Vasti is said to purge or calm vitiated Vata and further normalize its activities. Vasti is alleged to have a multifaceted activity that possesses preventative, curative, and promotional effects. As a result, it is recognized as the best course of therapy and a viable alternative to small surgeries. In contemporary medicine, enema is primarily used to remove feces from the large intestine, whereas in Ayurveda, Vasti is a route of drug administration for multiple actions, acting both locally in the large intestine and systemically on the body tissues, which is why it is considered to be a "Ardha chikitsa" as well as a "complete Chikitsa" due to its wider applicability and greater disease-curing ability. It ultimately comes to the conclusion that Vasti is the supreme and primary Panchakarma therapy method since it demonstrates broad spectrum action that may be used on a huge variety of disorders.